Green Synthesis, Characterization, and Antimicrobial Activity of Silver Nanoparticles Derived from Sargassum sp. (Ag-SE) - Adellia Ramadhani Putri Pratiwi; Heru Pramono; Mochammad Amin Alamsjah (Grouper, 2025)
The growing threat of antibiotic-resistant bacteria has led to a search for alternative antimicrobial agents, including nanotechnology. This study successfully synthesized silver nanoparticles (AgNPs) using aqueous extracts of Sargassum sp., a brown macroalgae species rich in bioactive compounds. The formation of the AgNPs was indicated by a visible color change from pale yellow to brown and was further confirmed by UV–Vis spectroscopy. This spectroscopy showed characteristic surface plasmon resonance peaks between 400 and 450 nm across concentrations ranging from 1 to 4 mM. Fourier-transform infrared (FT-IR) analysis revealed functional groups, such as hydroxyl (3888 cm⁻¹), carbonyl (around 3500 cm⁻¹), and aromatic C=C bonds (1635 cm⁻¹), which suggest a role in reducing and stabilizing the nanoparticles. We evaluated the antibacterial activity of the AgNPs against Escherichia coli, and Staphylococcus aureus using the disc diffusion method. At a concentration of 3 mM, the AgNPs inhibited E. coli with a maximum zone of inhibition of 3.90 mm and followed by S. aureus (3.35 mm). Although the inhibition zones were relatively narrow (<2 mm), the results demonstrate the AgNPs' selective antibacterial potential. The antibacterial mechanism likely involves membrane disruption, oxidative stress via reactive oxygen species (ROS) generation, and Ag⁺ ion release. These findings highlight Sargassum sp. as an eco-friendly and effective source for the green synthesis of AgNPs with promising applications in antimicrobial therapies.